A solar cell and its application

The silica nanospheres treated with acid can achieve low concentration self-assembly in perovskite solar cells, solving the problems of complexity and high cost of preparation of the interporous bracket layer of perovskite solar cells, and improving the photoelectric conversion efficiency and stability sex.

CN118829248BActive Publication Date: 2024-12-24CHINT NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411288279.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-24
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Existing perovskite solar cells have high cost and complex process steps in the thin film preparation process, especially the preparation method of three-dimensional orderly mesoporous scaffolding layer is complicated, resulting in increased costs during industrialization and unstable self-assembly at low concentrations. .

Method used

The acid-treated silica nanospheres are used as the nanosphere layer, and the formation of three-dimensional ordered nanosphere layers is achieved through low concentration self-assembly, improving the photoelectric conversion efficiency of the perovskite light absorbing layer and the repeatability and stability of the battery.

Benefits of technology

A three-dimensional ordered mesoporous scaffold layer self-assembled at low concentrations is realized, which improves the photoelectric conversion efficiency and stability of solar cells, simplifies the preparation process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118829248B_ABST
    Figure CN118829248B_ABST
Patent Text Reader

Abstract

The present invention provides a solar cell and its application, wherein the solar cell comprises a stacked substrate, an electron transport layer, a nanosphere layer, a perovskite light absorption layer, a hole transport layer and an electrode layer, wherein the perovskite light absorption layer is partially filled in the nanosphere layer; and the nanosphere layer comprises acid-treated silicon dioxide nanospheres. The nanosphere layer of the solar cell of the present invention comprises acid-treated silicon dioxide, which can realize self-assembly of the nanosphere layer at a low concentration, thereby obtaining a three-dimensional ordered nanosphere layer with a large specific surface area and a good electron transport channel, thereby improving the photoelectric conversion efficiency of the solar cell, and having good repeatability and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells and relates to a solar cell and application thereof. Background Art

[0002] Perovskite solar cells have the advantages of low preparation cost and can be prepared by solution method. In addition, the perovskite material of its absorption layer has excellent photoelectric properties, with outstanding advantages such as wide adjustable band gap, large absorption coefficient, long carrier diffusion length, high mobility and high defect tolerance. This has made perovskite solar cells quickly become a research hotspot at home and abroad. In less than ten years, the efficiency has soared from 3.8% photoelectric conversion efficiency at the beginning of 2009 to 26.14%. Its efficiency is comparable to that of traditional silicon cells. In addition, the preparation process of perovskite solar cells is relatively simple and the cost is lower, so it has a very broad application prospect.

[0003] The structure of a perovskite solar cell can be divided into a mesoporous structure and a planar structure. The perovskite solar cell with a mesoporous structure is composed of a transparent conductive substrate, an ETL layer (electron transport layer), a mesoporous support layer, and a perovskite light absorbing layer, a hole transport layer, and a counter electrode layer filled therein. CN 104409636A aims at the bottleneck problem that restricts the development of perovskite thin film solar cell technology, and discloses a perovskite thin film solar cell structure with a three-dimensional ordered mesoporous support layer and a preparation method thereof. The structure is composed of a transparent conductive substrate, a dense layer, a three-dimensional ordered mesoporous support layer, and a perovskite light absorbing layer, a hole transport layer, and a counter electrode layer filled therein. The three-dimensional ordered mesoporous support layer uses water-soluble colloidal crystals as templates to prepare a three-dimensional ordered mesoporous material. By adjusting the size of the template microspheres, a mesoporous support layer with controllable pore size can be prepared, thereby controlling the crystallization process of the perovskite film and the size of the grains. The method for preparing a three-dimensional ordered mesoporous support layer using a template method is cumbersome, with at least one more step, which will greatly increase the cost when industrialized.

[0004] Based on the above research, it is necessary to provide a solar cell with lower cost and a low-concentration self-assembled mesoporous scaffold layer. Summary of the invention

[0005] The object of the present invention is to provide a solar cell and its application. The nanosphere layer of the solar cell includes acid-treated silicon dioxide. When preparing the nanosphere layer, the silicon dioxide can maintain a low concentration of the solution for a long time to achieve self-assembly at a low concentration, thereby obtaining a three-dimensional ordered nanosphere layer with a large specific surface area and a good electron transmission channel, thereby improving the photoelectric conversion efficiency of the solar cell and having good repeatability and stability.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a solar cell, comprising a substrate, an electron transport layer, a nanosphere layer, a perovskite light absorption layer, a hole transport layer and an electrode layer arranged in layers, wherein the perovskite light absorption layer is partially filled in the nanosphere layer;

[0008] The nanosphere layer includes acid-treated silicon dioxide nanospheres.

[0009] The solar cell of the present invention includes a nanosphere layer between the electron transport layer and the perovskite light absorption layer, and the nanosphere layer includes acid-treated silicon dioxide nanospheres. The acid-treated silicon dioxide nanospheres can achieve low-concentration self-assembly, so that the nanosphere layer is a three-dimensional ordered mesoporous scaffold layer with a large specific surface area and good electron transport channels, thereby improving the photoelectric conversion efficiency of the solar cell and having good repeatability and stability.

[0010] Since the nanosphere layer of the present invention is a mesoporous support layer, the perovskite light-absorbing layer can be partially filled in the nanosphere layer.

[0011] Preferably, the thickness of the nanosphere layer is 100-300 nm, for example, 100 nm, 125 nm, 150 nm, 175 nm, 200 nm, 225 nm, 250 nm, 275 nm or 300 nm, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable, preferably 200-260 nm.

[0012] Preferably, the substrate comprises a glass conductive substrate, and the electrode layer comprises a metal electrode.

[0013] Preferably, the method for preparing the nanosphere layer comprises the following steps:

[0014] The acid-treated silica nanospheres are dispersed in water to obtain a silica nanosphere dispersion liquid, and the silica nanosphere dispersion liquid is coated and annealed to obtain the nanosphere layer.

[0015] The nanosphere layer was prepared by using acid-treated silica nanospheres to make the NH4 originally entrained in the SiO2 nanospheres + Can be H + Replacement, when dispersed in water again, these acid-treated SiO2 nanospheres maintain the low ion concentration of the solution for a long time, thereby ensuring a sufficiently strong repulsive force, achieving self-assembly at low concentrations, and obtaining a three-dimensional ordered mesoporous scaffold layer with a large specific surface area and good electron transmission channels, which improves the photoelectric conversion efficiency of solar cells and has good repeatability and stability.

[0016] Preferably, the concentration of the silica nanosphere dispersion is less than 10wt%, for example, it can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt% or 9wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1-5wt%.

[0017] In the prior art, the threshold concentration required for ordered self-assembly is 30 wt%. Below the threshold concentration, the dispersion is unstable. The preparation method of the present invention is not only simpler and less costly, but also can achieve self-assembly at a concentration as low as 1-5 wt%.

[0018] Preferably, the method for preparing the acid-treated silica nanospheres comprises the following steps:

[0019] The silicon dioxide nanospheres treated with acid are obtained by mixing the silicon dioxide nanospheres, water and acid, performing solid-liquid separation and washing.

[0020] Preferably, the silica nanospheres, water and acid are mixed until the solution pH is 1-4, for example, 1, 2, 3 or 4, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] Preferably, the mixing time is 10-20 hours, for example, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours or 20 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] The pH and time of the acid treatment of the present invention will affect the stability of the obtained silica nanosphere dispersion. If the pH of the acid treatment is too low or the time of the acid treatment is too long, the treatment effect is poor and the conductivity of the silica nanosphere dispersion increases. If the pH of the acid treatment is too high or the time of the acid treatment is too short, the treatment effect is poor and the stability of the silica nanosphere dispersion will decrease.

[0023] The present invention adopts water for washing, and the washing times are 2-4 times.

[0024] Preferably, the method for preparing the silicon dioxide nanospheres comprises the following steps:

[0025] The silicon dioxide nanospheres are obtained by mixing the silicon source, the solvent and the ammonium substance, performing solid-liquid separation and purification.

[0026] Preferably, the average diameter of the silica nanospheres is 20-150 nm, for example, 30 nm, 50 nm, 80 nm, 100 nm, 125 nm or 150 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] The silicon source includes TEOS (tetraethyl orthosilicate), the solvent includes alcohol and water, the ammonium substance includes ammonium hydroxide, and the mass ratio of the silicon source to the ammonium substance is 10:(0.2-0.5), for example, it can be 10:0.2, 10:0.3, 10:0.4 or 10:0.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the coating method includes spin coating, the number of spin coating is 1-3 times, for example, 1 time, 2 times or 3 times, the rotation speed is 1000-3000rpm, for example, 1000rpm, 2000rpm or 3000rpm, and the time is 20-40s, for example, 20s, 30s or 40s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the annealing temperature is 150-250°C, such as 150°C, 200°C or 250°C, and the annealing time is 20-40min, such as 20min, 30min or 40min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the method for preparing the nanosphere layer comprises the following steps:

[0031] (1) After mixing a silicon source, a solvent and an ammonium substance, solid-liquid separation and purification, the silicon dioxide nanospheres are obtained; the silicon source comprises TEOS, the solvent comprises alcohol and water, the ammonium substance comprises ammonium hydroxide, and the mass ratio of the silicon source to the ammonium substance is 10:(0.2-0.5);

[0032] (2) mixing the silica nanospheres, water and acid described in step (1) until the pH value of the solution is 1-4, stirring for 10-20 hours, separating the solid and the liquid, and washing to obtain acid-treated silica nanospheres;

[0033] (3) dispersing the acid-treated silica nanospheres in water to obtain a silica nanosphere dispersion having a concentration of 1-5 wt %, and coating and annealing the silica nanosphere dispersion to obtain a nanosphere layer having a thickness of 200-260 nm.

[0034] In a second aspect, the present invention provides an electrical device, wherein the electrical device comprises the solar cell as described in the first aspect.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The present invention adopts acid-treated silicon dioxide nanospheres as the nanosphere layer. The acid-treated silicon dioxide can realize low-concentration self-assembly, so that the nanosphere layer is a three-dimensional ordered mesoporous scaffold layer with a large specific surface area and good electron transmission channels, thereby improving the photoelectric conversion efficiency of the solar cell, and having good repeatability and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram of the structure of the solar cell according to Embodiment 1 of the present invention;

[0038] Among them, 1-glass conductive substrate, 2-electron transport layer, 3-nanosphere layer, 4-perovskite absorption layer, 5-hole transport layer, 6-metal electrode. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0040] Example 1

[0041] This embodiment provides a Figure 1 The solar cell shown is a mesoporous perovskite solar cell, which includes a stacked glass conductive substrate 1, an electron transport layer 2, a nanosphere layer 3, a perovskite absorption layer 4, a hole transport layer 5 and a metal electrode 6, wherein the perovskite absorption layer 4 is partially filled in the nanosphere layer 3;

[0042] The preparation method of the nanosphere layer comprises the following steps:

[0043] (i) 196 mL of ethanol, 20 mL of microporous water, and 1.3 mL of ammonium hydroxide (28 wt%) were mixed in a 250 mL flask. After magnetic stirring for 5 min, 10 mL of TEOS was injected. The mixture was stirred at 300 rpm for 15 h at room temperature and then centrifuged at 11,000 rpm for 15 min to separate the nanospheres from the reaction mixture. The product was further purified twice with ethanol and water to remove any reaction residues to obtain silica nanospheres with an average diameter of 50 nm.

[0044] (ii) dispersing the silica nanospheres prepared in step (i) in 50 mL of water, and then adding a hydrochloric acid solution (1 mol / L) to adjust the pH value of the dispersion to 4, and stirring the dispersion at room temperature for 15 h, and then separating the nanospheres from the original acid-treated solution by centrifugation, and re-dispersing them in 60 mL of fresh water by ultrasonic treatment, and repeating the same centrifugation and re-dispersion with water for 3 times, and obtaining a silica nanosphere dispersion with a concentration of 1 wt% when the silica nanoparticles are completely dispersed in water in each washing cycle;

[0045] (iii) The silicon dioxide nanosphere dispersion prepared in step (ii) was spin-coated on the titanium dioxide layer at a rotation speed of 2000 rpm for 30 seconds, the spin coating was repeated twice, and then annealed at 200° C. for 30 minutes to obtain a nanosphere layer 3 with a thickness of 230 nm.

[0046] The method for preparing the solar cell comprises the following steps:

[0047] (1) Cleaning the glass conductive substrate

[0048] ITO glass was used as a conductive substrate, and glass cleaner, deionized water, ethanol, acetone, isopropanol, and ethanol were ultrasonically treated for 15 min in sequence, the substrate was dried with dry air, and then treated with UV-ozone for 20 min.

[0049] (2) Preparation of electron transport layer

[0050] A 0.15 M solution of titanium bis(acetylacetonate) diisopropoxide in 1-butanol solution (75% w / w isopropanol, Aldrich) was coated on the ITO glass at 2500 rpm / 30 s and then heated at 125 °C for 5 min to prepare a compact titanium dioxide layer.

[0051] (3) preparing a nanosphere layer by using the above-mentioned method for preparing a nanosphere layer;

[0052] (4) Preparation of perovskite light-absorbing layer

[0053] The perovskite precursor solution was prepared in advance. 1.53M PbI2, 1.4M FAI, 0.5M MACl, and 0.0122M (0.8 mol%) of MABr and PbBr2 in an equal molar ratio were mixed in DMF:DMSO=8:1 to prepare the perovskite solution. The perovskite precursor solution was dripped on the surface of the support layer at 1000 rpm / 10 s, 5000 rpm / 30s, and after 5000 rpm for 10s, 600μL of ether solution was deposited on the substrate. Then, the perovskite substrate was annealed at 150 °C for 20min. After annealing, the sample was transferred to the glove box.

[0054] (5) Preparation of hole transport layer

[0055] The preparation method of the doped Spiro-OMeTAD solution is as follows: first prepare the Li-TFSI solution, dissolve 520 mg / mL in acetonitrile, then measure 72.3 mg Spiro-OMeTAD powder, 28.8 µL tBp solution and 17.5 µL Li-TFSI solution in 1 mL chlorobenzene, stir to prepare 1 mL Spiro-OMeTAD solution, and spin coat the prepared Spiro-OMeTAD solution on the perovskite surface using a spin coating method at 3000 rpm / 30s.

[0056] (6) Evaporated silver metal electrode

[0057] The metal electrode was prepared by thermal evaporation. First, the prepared sample was placed on the mask plate, then placed in the evaporation box slot, the program was set up and evaporation began, and a silver electrode with a thickness of about 120 nm was vacuum deposited.

[0058] Example 2

[0059] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0060] The preparation method of the nanosphere layer comprises the following steps:

[0061] (i) 196 mL of ethanol, 20 mL of microporous water, and 1.3 mL of ammonium hydroxide (28 wt%) were mixed in a 250 mL flask. After magnetic stirring for 5 min, 10 mL of TEOS was injected. The mixture was stirred at 300 rpm for 15 h at room temperature and then centrifuged at 11,000 rpm for 15 min to separate the nanospheres from the reaction mixture. The product was further purified twice with ethanol and water to remove any reaction residues to obtain silica nanospheres with an average diameter of 50 nm.

[0062] (ii) dispersing the silica nanospheres in step (i) in 50 mL of water, then adding a hydrochloric acid solution (1 mol / L) to adjust the pH value of the dispersion to 2.5, keeping the dispersion stirred at room temperature for 20 h, then separating the nanospheres from the original acid-treated solution by centrifugation, and re-dispersing them in 60 mL of fresh water by ultrasonic treatment, and repeating the same centrifugation and re-dispersion with water for 3 times, and obtaining a silica nanosphere dispersion with a concentration of 3 wt% when the silica nanoparticles are completely dispersed in water in each washing cycle;

[0063] (iii) spin coating the silica nanosphere dispersion in step (ii) on the titanium dioxide layer at a rotation speed of 3000 rpm for 20 seconds, spin coating twice, and then annealing at 250° C. for 20 minutes to obtain a mesoporous scaffold layer with a thickness of 200 nm.

[0064] Example 3

[0065] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0066] The preparation method of the nanosphere layer comprises the following steps:

[0067] (i) 196 mL of ethanol, 20 mL of microporous water, and 1.3 mL of ammonium hydroxide (28 wt%) were mixed in a 250 mL flask. After magnetic stirring for 5 min, 10 mL of TEOS was injected. The mixture was stirred at 300 rpm for 15 h at room temperature and then centrifuged at 11,000 rpm for 15 min to separate the nanospheres from the reaction mixture. The product was further purified twice with ethanol and water to remove any reaction residues to obtain silica nanospheres with an average diameter of 50 nm.

[0068] (ii) dispersing the silica nanospheres in step (i) in 50 mL of water, then adding a hydrochloric acid solution (1 mol / L) to adjust the pH value of the dispersion to 1, keeping the dispersion stirred at room temperature for 10 h, then separating the nanospheres from the original acid-treated solution by centrifugation, and re-dispersing them in 60 mL of fresh water by ultrasonic treatment, and repeating the same centrifugation and re-dispersion with water for 3 times, and obtaining a silica nanosphere dispersion with a concentration of 5 wt% when the silica nanoparticles are completely dispersed in water in each washing cycle;

[0069] (iii) spin coating the silica nanosphere dispersion in step (ii) on the titanium dioxide layer at a rotation speed of 1000 rpm for 40 seconds, spin coating twice, and then annealing at 150° C. for 40 minutes to obtain a mesoporous scaffold layer with a thickness of 260 nm.

[0070] Example 4

[0071] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0072] The method for preparing the nanosphere layer is the same as that of Example 1 except that the pH value of the dispersion is adjusted to 0.5 in step (ii) to adapt the obtained silica nanosphere dispersion to a change in pH.

[0073] Example 5

[0074] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0075] The method for preparing the nanosphere layer is the same as that of Example 1 except that the pH value of the dispersion is adjusted to 5 in step (ii) to adapt the obtained silica nanosphere dispersion to a different pH.

[0076] Example 6

[0077] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0078] The method for preparing the nanosphere layer is the same as that of Example 1, except that the dispersion is stirred for 5 hours in step (ii) to allow the obtained silica nanosphere dispersion to adapt to changes.

[0079] Example 7

[0080] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0081] The method for preparing the nanosphere layer is the same as that of Example 1, except that the dispersion is stirred for 25 hours in step (ii) to allow the obtained silica nanosphere dispersion to adapt.

[0082] Example 8

[0083] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0084] The method for preparing the nanosphere layer is the same as that of Example 1 except that the concentration of the silica nanosphere dispersion in step (ii) is 0.7 wt %.

[0085] Example 9

[0086] This embodiment provides a solar cell, which is the same as Embodiment 1 except that the preparation method of the nanosphere layer is different;

[0087] The method for preparing the nanosphere layer is the same as that of Example 1 except that the concentration of the silica nanosphere dispersion in step (ii) is 7 wt %.

[0088] Comparative Example 1

[0089] This comparative example provides a solar cell, which is the same as Example 1 except that the nanosphere layer includes titanium dioxide nanospheres, and the rest is the same as Example 1;

[0090] The preparation method of the nanosphere layer comprises the following steps:

[0091] Under argon protection, 5 mL of water, 1 g of acrylamide, 1.5 g of surfactant Span 80, 1.5 g of surfactant Tween 80, and 20 mL of cyclohexane were added to a three-necked flask. After the system was stirred evenly, it was heated to 30 ° C, and then 0.00125 g of ammonium persulfate was added. After the reaction was stopped after 5 h, the obtained emulsion was centrifuged at 5000 rpm to obtain a monodisperse polyacrylamide colloidal crystal template with a particle size of 40-50 nm; the prepared polyacrylamide colloidal crystal template was spin-coated on a FTO substrate with a dense TiO2 layer, and a mixture of 4.2 mL of tetrabutyl titanate, 0.3 mL of hydrochloric acid (concentration 37 wt%), 0.8 mL of H2O and 4.2 mL of anhydrous ethanol was added and the template was immersed. After soaking for 1 h, it was placed in a 30 ° C oven for polymerization reaction for 48 h. After the reaction was completed, it was cleaned with deionized water and anhydrous ethanol, and vacuum dried at 70 degrees for 3 h to obtain a substrate with a 3DOM TiO2 mesoporous support layer.

[0092] Comparative Example 2

[0093] This comparative example provides a solar cell, which is the same as Example 1 except that the nanosphere layer includes silicon dioxide nanospheres that have not been acid-treated, and the rest is the same as Example 1;

[0094] The method for preparing the nanosphere layer is the same as that of Example 1 except that the acid treatment is not performed in step (ii) and the concentration of the silica nanosphere dispersion is 30 wt %.

[0095] The solar cells provided in the above embodiments and comparative examples were subjected to performance tests. The test method included using an IV test instrument to test the cells under a standard sunlight AM1.5G spectrum. The test results are shown in Table 1:

[0096] Table 1

[0097]

[0098] From Table 1 we can see that:

[0099] It can be seen from Examples 1-3 and Comparative Examples 1-2 that the preparation method of the present invention has a simple process, especially fewer steps than Comparative Application Example 1, low cost, and can also improve the performance of solar cells; it can be seen from Example 1 and Examples 4-7 that the pH and time of the acid treatment of the present invention will affect the effect of the acid treatment, thereby affecting the dispersion of the silica nanospheres and affecting the battery performance; it can be seen from Example 1 and Examples 8-9 that the concentration of the silica nanosphere dispersion of the present invention will affect the performance of the mesoporous support layer, thereby affecting the battery performance.

[0100] In summary, the present invention provides a solar cell and its application. The nanosphere layer of the solar cell includes acid-treated silica, which can achieve self-assembly of the nanosphere layer at a low concentration, thereby obtaining a three-dimensional ordered nanosphere layer with a large specific surface area and a good electron transmission channel, thereby improving the photoelectric conversion efficiency of the solar cell and having good repeatability and stability.

[0101] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A solar cell, characterized in that: The solar cell comprises a stacked substrate, an electron transport layer, a nanosphere layer, a perovskite light absorption layer, a hole transport layer and an electrode layer, wherein the perovskite light absorption layer is partially filled in the nanosphere layer; The nanosphere layer comprises acid-treated silicon dioxide nanospheres, and the raw materials for preparing the acid-treated silicon dioxide nanospheres include NH 4+ Silica nanospheres; The nanosphere layer is a three-dimensional ordered mesoporous scaffold layer.

2. The solar cell according to claim 1, characterized in that The thickness of the nanosphere layer is 100-300nm.

3. The solar cell according to claim 1, characterized in that The method for preparing the nanosphere layer comprises the following steps: The acid-treated silica nanospheres are dispersed in water to obtain a silica nanosphere dispersion liquid, and the silica nanosphere dispersion liquid is coated and annealed to obtain the nanosphere layer.

4. The solar cell according to claim 3, characterized in that: The concentration of the silica nanosphere dispersion is less than 10 wt %.

5. The solar cell according to claim 3 or 4, characterized in that: The method for preparing the acid-treated silica nanospheres comprises the following steps: The silicon dioxide nanospheres treated with acid are obtained by mixing the silicon dioxide nanospheres, water and acid, performing solid-liquid separation and washing.

6. The solar cell according to claim 5, characterized in that The silica nanospheres, water and acid are mixed until the solution pH is 1-4; The mixing time is 10-20 hours.

7. The solar cell according to claim 5, characterized in that: The method for preparing the silicon dioxide nanospheres comprises the following steps: The silicon dioxide nanospheres are obtained by mixing the silicon source, the solvent and the ammonium substance, performing solid-liquid separation and purification; The average diameter of the silicon dioxide nanospheres is 20-150 nm; The silicon source includes TEOS, the solvent includes alcohol and water, the ammonium substance includes ammonium hydroxide, and the mass ratio of the silicon source to the ammonium substance is 10:(0.2-0.5).

8. The solar cell according to claim 3, characterized in that: The coating method includes spin coating, the number of spin coating is 1-3 times, the rotation speed is 1000-3000rpm, and the time is 20-40s; The annealing temperature is 150-250° C. and the annealing time is 20-40 min.

9. The solar cell according to claim 3, characterized in that: The method for preparing the nanosphere layer comprises the following steps: (1) After mixing a silicon source, a solvent and an ammonium substance, solid-liquid separation and purification, the silicon dioxide nanospheres are obtained; the silicon source comprises TEOS, the solvent comprises alcohol and water, the ammonium substance comprises ammonium hydroxide, and the mass ratio of the silicon source to the ammonium substance is 10:(0.2-0.5); (2) mixing the silica nanospheres, water and acid described in step (1) until the pH value of the solution is 1-4, stirring for 10-20 hours, separating the solid and the liquid, and washing to obtain acid-treated silica nanospheres; (3) dispersing the acid-treated silica nanospheres in water to obtain a silica nanosphere dispersion having a concentration of 1-5 wt %, and coating and annealing the silica nanosphere dispersion to obtain a nanosphere layer having a thickness of 200-260 nm.

10. An electrical device, characterized in that: The electrical device comprises the solar cell according to any one of claims 1 to 9.